2014
DOI: 10.1039/c4tb00165f
|View full text |Cite
|
Sign up to set email alerts
|

pH-responsive hydrogel cubes for release of doxorubicin in cancer cells

Abstract: Doxorubicin (DOX)-loaded poly(methacrylic acid) hydrogel cubes release the drug at pH <5. These hydrogels are developed for shape-directed cellular uptake for drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 91 publications
(85 reference statements)
4
83
0
Order By: Relevance
“…The (PMAA CS ) 5 hydrogel particles showed a swelling profile similar to that of our previously demonstrated nondegradable EDA-linked hydrogel particles. 16 However, the overall swelling ratios (the ratio of the particle size at a certain pH to the minimum size of the hydrogel particle at pH = 5) were smaller than those of the EDA-crosslinked cubes or spheres, which underwent a nearly twofold reversible swell/shrink response to pH variations. 16 The lower 1.5−1.2-fold swelling ratios of the (PMAA CS ) 5 biodegradable hydrogels can be explained by a more hydrophobic nature of those structures because of a more hydrophobic CS linker as discussed above for planar PMAA CS hydrogels.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…The (PMAA CS ) 5 hydrogel particles showed a swelling profile similar to that of our previously demonstrated nondegradable EDA-linked hydrogel particles. 16 However, the overall swelling ratios (the ratio of the particle size at a certain pH to the minimum size of the hydrogel particle at pH = 5) were smaller than those of the EDA-crosslinked cubes or spheres, which underwent a nearly twofold reversible swell/shrink response to pH variations. 16 The lower 1.5−1.2-fold swelling ratios of the (PMAA CS ) 5 biodegradable hydrogels can be explained by a more hydrophobic nature of those structures because of a more hydrophobic CS linker as discussed above for planar PMAA CS hydrogels.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…The viability of A549 and HeLa cancer cells was significantly decreased upon interaction with DOX-loaded cubic hydrogels. [11] Anirudhan et al [12] prepared a gelatin-based pH-responsive composite hydrogel by grafting b-cyclodextrin (b-CD) to gelatin (Gel) and crosslinking with oxidized dextran (OX-Dex), and the as-prepared pH-sensitive b-CD-grafted Gel crosslinked with OX-Dex (b-CD-g-Gel/OX-Dex) or composite hydrogel (CHG) was used to investigate the colon delivery of the anticancer drug 5-fluorouracil (5-FLU). They found that the grafting of b-CD enhanced the drug encapsulation capacity and that the drug release profile followed the Higuchi model.…”
Section: Organic-materials-based Ph-responsive Drug-delivery Systemsmentioning
confidence: 97%
“…The DOX-loaded hydrogels could be taken up quickly by human glioma through endocytosis and then bi-odegraded to release the loaded drug, which led to a good antitumor efficacy. [10] Kozlovskaya et al [11] reported on a novel type of hydrogel microparticle that underwent large, rapid, and reversible volume changes in response to the pH value. They prepared cubic hydrogels as interconnected poly(methacrylic acid) network replicas of mesoporous manganese oxide templates by sequential infiltration of poly(methacrylic acid) and poly(N-vinylpyrrolidone), followed by crosslinking of poly(-methacrylic acid) and template dissolution.…”
Section: Organic-materials-based Ph-responsive Drug-delivery Systemsmentioning
confidence: 98%
“…Among stimulus-sensitive hydrogels, pH-responsible hydrogels, derived from both natural and synthetic polymers, have been investigated intensively [16,17]. This unique class of hydrogels may find significant applications.…”
Section: Introductionmentioning
confidence: 99%